Transformation-toughened zirconia: An overview - Pathak, B; Maskey, B; Bhochhibhoya, A; Devkota, D (Journal of Nepalese Prosthodontic Society, 2022)
Zirconia is a “metastable” ceramic, consisting of monoclinic, tetragonal, and cubic phases. Partially stabilized zirconia is preferred choice for dental use since they offer the opportunity to fabricate prosthesis which is not available with other ceramic materials. Phase transformation in zirconia ceramics represents one of the most remarkable innovations in the ceramic field. This phase transformation can have desirable consequences, increase in crack growth resistance which is referred to as “phase transformation toughening”. However, the phase-induced volumetric transformation can also have disastrous consequences, if not properly controlled. This article provides information on crystallography of zirconia and the main characteristics of the tetragonal to monoclinic transformationand also discusses the positive (transformation toughening) and negative aspects (ageing/LTD) of the tetragonal to monoclinic transformation.